En Route to Revolution: The Communists and the Free Officers—Honeymoon and Separation. Issue 4 (1st October 2016) - Ginat, Rami; Alon, Odelya
Abstract: Organized communism had already emerged in Egypt shortly after the Bolshevik revolution in Russia. Afterwards, it was characterized by internal splits and rivalries, which were followed by constant persecutions by the authorities. Nevertheless, revolutionary platforms presented by communists gradually seeped into government policy and thinking, noticeably after the July 1952 revolution. This study sheds new light on the causes for the formation of the complex relations between Egypt's military regime and the communist movement. The intimate working relations and clandestine cooperation between the Free Officers and the largest communist organization, the Democratic Movement for National Liberation, proved to be constructive and, more importantly, successful, following the military takeover of 23 July. However, the Officers–Communists honeymoon was ephemeral and the ad-hoc alliance disintegrated shortly thereafter. Based on untapped exclusive first-hand sources drawn from a variety of archives, including Egyptian and Russian, this article provides a new narrative to the origins of one of the most studied subjects in the modern history of the Middle East—the Egyptian July 1952 revolution.